Fructan extracts from wheat stem and barley grain stimulate large bowel fermentation in rats - Belobrajdic, Damien P.; Jenkins, Colin L.D.; Bushell, Rhys; Morell, Matthew K.; Bird, Anthony R. (Nutrition research (New York, N.Y.), 2012)
The benefits of inulin-type fructans for bowel health are well established, but less so for other fructan sources. In vitro data suggest that fructans extracted from cereals are readily fermented and produce favorable short-chain fatty acid profiles; however, whether this occurs in vivo is unknown. We hypothesized that in rats, fructans extracted from wheat stem and barley grain would have similar effects on fermentation as oligofructose (OF). Fifty-six male Sprague-Dawley rats were randomly assigned to 1 of 7 dietary treatments that contained either 2% or 5% fructan, provided by a barley grain fructan extract (BGFE), a wheat stem fructan extract, or OF or no added fructan (control). The duration of the feeding study was 14 days. Rats fed diets containing 5% fructan had higher cecal digesta weights; larger acetate, propionate, and total short-chain fatty acid pools; and lower pHs in comparison with the control group. In addition, only the 5% OF and 5% BGFE groups increased cecal butyrate pools, and 5% BGFE was the only group in which colonic digesta pH was lower than that of the control. Diets containing 2% fructan did not affect any of these fermentation end points. Whereas bifidobacteria numbers in cecal digesta of 2% and 5% OF were higher than that in the control group, they were not different from those in rats fed diets containing BGFE and wheat stem fructan extract. Barley grain and wheat stem fructans produced similar large bowel fermentation patterns to OF when fed to rats at 5% of the diet.